2002
DOI: 10.1093/carcin/23.7.1111
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage in lung epithelial cells isolated from rats exposed to quartz: role of surface reactivity and neutrophilic inflammation

Abstract: Respirable quartz has been classified as a human lung carcinogen (IARC, 1997). However, the mechanisms involved in quartz-induced carcinogenesis remain unclear. The aim of the present study was to investigate acute DNA damage in epithelial lung cells from rats exposed to quartz. Since surface reactivity is considered to play a crucial role in the toxicity of quartz, the effect of surface modifying agents polyvinylpyridine-N-oxide (PVNO) and aluminium lactate (AL) was evaluated. Therefore, rats were instilled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 68 publications
3
73
1
Order By: Relevance
“…Similar findings were reported by Knaapen et al (2002) in rats and by Schins et al (2002) using A549 culture cells. These studies indicated that DNA strand breakage occurred more readily with exposure to crystallite silica; that is, such exposure leads to the production of more urinary 8-OHdG.…”
Section: Possible Mechanismssupporting
confidence: 91%
“…Similar findings were reported by Knaapen et al (2002) in rats and by Schins et al (2002) using A549 culture cells. These studies indicated that DNA strand breakage occurred more readily with exposure to crystallite silica; that is, such exposure leads to the production of more urinary 8-OHdG.…”
Section: Possible Mechanismssupporting
confidence: 91%
“…We specifically applied type II cells, since this is the cell type from which (rat) lung tumours are most probably derived after chronic particle exposure (33). Although our findings may very well have implications for other organs where neutrophil influx is accompanied by an accumulation of nitrite, we specifically focused on the lung epithelium because of several reasons: (i) neutrophils are recognized as crucial effector cells in the pathogenicity of pulmonary inflammation (34,35), (ii) we and others showed that DNA strand breakage and mutagenicity in pulmonary epithelium of (particle-treated) rats was closely related to neutrophil influx (6,15,36), (iii) pulmonary inflammation is characterized by the release of the MPO substrate H 2 O 2 (37) and (iv) mainly by the presence of alveolar macrophages, the lung contains a potent source of nitrite (19,21,22). We demonstrated that nitrite significantly enhances neutrophil-induced DNA strand breakage in co-cultured epithelial cells.…”
Section: Discussionmentioning
confidence: 98%
“…In silicosis, lung neutrophils have an important role in the development of cellular and DNA injury (41,42), and several studies proposed that radicals and enzymes produced by neutrophils lead to lung destruction and cancer (43,44). Activated macrophages and epithelial cells release proinflammatory mediators that induce neutrophil differentiation from the hematopoietic progenitors, their recruitment, and activation inside the inflamed lung tissue (45).…”
Section: Discussionmentioning
confidence: 99%